Age-Friendly Hospital Environments: Qualitative Exploration of the Senior Citizens and Care Providers’ Perspectives - Shrestha, Krishna Devi; KC, Takma; Bista, Archana Pandey; Manandhar, Saraswati (Journal of Institute of Medicine Nepal, 2025)
Introduction Age-friendly hospital environments, and quality care are very crucial for maintaining the health and well-being of older adults. Globally, despite the growing concerns of age-friendly environment, limited research exists on how the senior citizens and their caregivers perceive the hospital environments. Hence, this study explores their perspectives to inform improvements in providing age- friendly care and services. Methods Descriptive phenomenological qualitative research was conducted at two tertiary-level hospitals in Nepal. A total of 28 participants were selected purposively and data were collected through in-depth interview using semi-structured interview guidelines and analysis was done by following Colaizzi's 7-steps of qualitative data analysis method. Results Four main themes were extracted from the data analysis :‘need to access healthcare facilities;’ ‘urgent need for expansion of age-friendly hospital services;’ ‘the age-friendly physical environment; ‘need for information, education, and effective communication in an age-appropriate manner. Participants expected for the availability of transportation facilities, affordable/free hospital services, priority, and prompt services with adequate facilities. Additionally, participants emphasized on continuous presence of care givers, a separate, no queues and digital payment system in billing counter, timely information, a separate geriatric ward/OPD with age-friendly physical infrastructure with religious and spiritual support as essential elements of an age-friendly environment. Conclusion This study highlights the need to create age-friendly hospital environment through development, implementation, promotion of policies, infrastructures, and age-sensitive approaches to enhance the well-being of senior citizens.